Interaction between physical demands and job strain on musculoskeletal symptoms and work performance. Issue 1 (2nd January 2023) - Kwon, Suyoung; Lee, Soo-Jeong; Bao, Stephen; de Castro, A. B.; Herting, Jerald R.; Johnson, Kurt
Abstract: This study investigated the interaction between physical demands and job strain on musculoskeletal symptoms in upper extremities (MSUE) and work performance. Two years of prospective data were analysed from 713 full-time workers from twelve manufacturing and healthcare facilities in Washington in the United States. Physical exposure was measured by the Strain Index and Threshold Limit Value for hand activity, giving rise to safe, action, and hazardous physical demand groups. Job strain was calculated as the ratio of psychological job demands to job control. Multilevel modelling analysis showed that job strain affected MSUE and limited work performance less in the high physical demand group than the safe group because the protective effect of job control was smaller in these groups. Findings may suggest that high physical demand jobs are structured such that workers have low job control or high physical demand groups experience job strain not adequately captured by psychosocial variables. Practitioner Summary: The effects of job strain and job control on musculoskeletal symptoms in upper extremities and work performance were smaller among workers with higher physical demands. This could imply that high physical demand jobs limit job control or psychosocial variables may not adequately capture job strain among high physical demand groups.